Optimalisasi Praktik Perawat Dalam Pencegahan Cedera Jarum Suntik - Wibowo, Nurhadi; Hanny Handiyani (PT. Pubsains Nur Cendekia, 2023)
Nurses as the person in charge of nursing care must ensure safe behavior while working, one of which is from the occurrence of needlestick injuries. The purpose of this paper is to identify the impact of optimizing nurse practice in the prevention of needlestick injuries. The author observed the behavior of nurses by using Standard Operating Procedures (SPO) to administer drugs through intravenous. Optimization of nurses' practices through interactive discussions on the prevention of needlestick injuries during pre-conferences. The results of optimizing nurses' practices in giving drugs through intravenous complete according to SPO. It is recommended that optimization of nurse practice is important to prevent needlestick injuries.